KUALITAS PELAYANAN INSTITUSI PENDIDIKAN TERHADAP KEPUASAN SISWA SMK NEGERI 4 MALANG - Aman Santoso; Widi Dewi Ruspitasari; Moh. Bukhori (Unitri Press, 2021)
This study aims to determine how the service quality of educational institutions on student satisfaction at SMK Negeri 4 Malang. The sample that has been used were all students of class XI SMKN 4 Malang taken through a total sampling technique in order to obtain 260 students. Collec ted data through observation, interviews and questionnaires by testing the quality of service through five variable indicators, namely tangible, reliability variable, responsiveness variable, assurance variable, and empathy variable using Likert scale. The results of this study was indicate that the tangible, reliability and responsiveness variables have a negative and insignificant ef fect, while the assurance and sympathy variables have a positive influence on student satisfaction at SMKN 4 Malang. This is because the guarantee is able to provide feedback to students by providing trust and a sense of security, while the empathy variable is able to provide a sense of comfort in understanding the needs of students so that they can provide service satisfaction for SMKN 4 Malang students in these two aspects.